Federalism in China and Russia story of success and story of failure? - Libman, Alexander (Cheltenham Edward Elgar Publishing, 2018)
Based on the synthesis of a large empirical and theoretical literature on center-region relations in China and Russia, Federalism in China and Russia is one of the first attempts to integrate this literature from different disciplines into a coherent common framework. Libman and Rochlitz argue that the divergence in growth performance between Russia and China can be - at least partially - explained by a number of features of the Chinese system of center-regional relations.
Includes bibliographical references and index.
Keywords: Central-local government relations